Extrovert versus Introvert Students: What EFL Learning Strategy do They Use? - Eko Noprianto (Lecturer Association of Linguistics, Language Teaching, and Literature Studies in Indonesi, 2017)
Since Indonesian students come from different cultures, languages and personality traits as well, recognizing their personality traits and their language learning strategy choice might be effective to help teacher design an effective teaching strategies to achieve learning objectives. This study was intended to find out (1) what personality traits Indonesian senior high school students fell into, and (2) to investigate what language learning strategies introvert and extrovert students used highly frequently. The 58 participants aged from sixteen to eighteen years old who were from the third grade of senior high school and were all from science class were given eighteen statements of McCroskey’s introversion scale to categorize them into extrovert and introvert and were administered with 32 statements of English Language Learning Strategy Inventory or ELLSI to see their learning strategy. The data were analyzed by means of descriptive statistics in terms of mean frequencies and statistical differences. The finding revealed that majority of senior high school students majoring science study program fell into introvert with 89.6% (52 students). Besides, extrovert students used more language learning strategy highly frequently than introvert students with eight items compared to introvert students with only five items. Interestingly, both extrovert and introvert students share four strategy items in common. Although it is statistically not significant (ρ > 0.05), the finding also shows that extrovert students seemed to use affective strategy more than introverts who used memory strategy highly frequently.